Mental Health Status and Factors that Influence the Course of Graves’ Disease and Antithyroid Treatments - Chen, D. Y.; Schneider, P. F.; Zhang, X. S.; He, Z. M.; Jing, J.; Chen, T. H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Biological, psychological and social factors may interact with the mental health status of Graves’ disease (GD) patients before and after antithyroid drug (ATD) treatment. Our aim was to quantify the impact of supportive and risk factors after recovery from GD which may enhance cure rates.300 patients were recruited for a 6-year prospective cohort study. Before and after treatment, we assessed the impact of biopsychosocial factors on the success of ATD treatment and mental health using the Symptom Checklist 90, the Eysenck Personality Questionnaire, the Life Event Scale, Simplified Coping Styles and the Perceived Social Support Scale. The patients routinely received ATD at least over 18 months. End-point was defined as cured (at least 2 years without a relapse after the withdrawal of ATD), otherwise as not cured.Regression analysis explained 80.5% of the influences affecting mental health. The odds ratios (OR) revealed positive coping styles (OR: 2.90, 95% CI, 1.09–7.68), negative events (OR: 1.04, 95% CI, 1.01–1.07) and social support (OR: 5.10, 95% CI, 2.77–9.40) as protective factors, predicting a cure for GD patients. These variables explained 61.7% of the influences leading to a cure or no cure. Large thyroid volume was a risk factor, predicting failure (OR: 0.865, 95% CI, 0.83–0.90, P<0.000).Enhancing positive coping strategies and social support is important to improve mental health in GD patients, to avoid compromising work-related performance and endangering a patient’s social status.
Keywords: thyroid autoimmunity; thyroiditis autoimmunity; thyrotropin hormones